Торгівля Північного Приазов'я у першій половині ХІХ ст. (за матеріалами газети "Одеський вісник"). (Zaporizhzhia Historical Review, 2021)
The article explores the full spectrum of trade relations in North Trans-Azov territories (Priazovye), including Berdyansk, in the first half of XIXth century, together with the factors of situating internal and specificity of external trade in the region, basing upon the materials from “Odessa Herald” (“Odessky Visnyk”) publications.